2019
DOI: 10.1038/s41598-019-51092-1
|View full text |Cite
|
Sign up to set email alerts
|

Concentrates of two subsets of extracellular vesicles from cow’s milk modulate symptoms and inflammation in experimental colitis

Abstract: Extracellular vesicles (EVs) are involved in cell-to-cell communication and modulation of numerous physiological and pathological processes. EVs are found in large quantities in milk and contain several inflammation- and immunity-modulating proteins and microRNAs, through which they exert beneficial effects in several inflammatory disease models. Here, we investigated the effects of two EV subsets, concentrated from commercial cow’s milk, on a murine model of colitis induced with dextran sodium sulfate (DSS). … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

4
39
0

Year Published

2020
2020
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 47 publications
(49 citation statements)
references
References 108 publications
4
39
0
Order By: Relevance
“…It had been reported that mEVs were bioavailable, biologically active compounds that played a key role in the regulation of intestinal immune homeostasis, intestinal barrier protection, and DSS‐induced colitis. [ 41,52,53 ] In our study, the results indicated that the expression level of Muc2, RegIIIγ, Myd88, and GATA4 genes in the intestinal epithelium of mice by oral administration mEVs was increased significantly. MUC2 could be up‐regulated by butyrate and provide a protective barrier between the epithelial surfaces and the gut lumen.…”
Section: Discussionsupporting
confidence: 52%
See 2 more Smart Citations
“…It had been reported that mEVs were bioavailable, biologically active compounds that played a key role in the regulation of intestinal immune homeostasis, intestinal barrier protection, and DSS‐induced colitis. [ 41,52,53 ] In our study, the results indicated that the expression level of Muc2, RegIIIγ, Myd88, and GATA4 genes in the intestinal epithelium of mice by oral administration mEVs was increased significantly. MUC2 could be up‐regulated by butyrate and provide a protective barrier between the epithelial surfaces and the gut lumen.…”
Section: Discussionsupporting
confidence: 52%
“…It was reported in the recent study that the abundance of Lachnospiraceae and Ruminococaccae were significantly increased in mice rich in milk EVs diet. [ 40,41 ] It could be due to changes in the gut microbial community caused by fraction of milk EVs that escape absorption. [ 42 ] Lachnospiraceae and Ruminococcaceae were two of the most abundant families from the Order Clostridiales and had been associated with the maintenance of gut health.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Furthermore, the study also reported the uptake of bovine milk EVs by murine macrophages [ 81 ]. Whilst the protein cargo in milk EVs from humans, cows and pigs are known to be contributed majorly by mammary epithelial cells, numerous other proteins expressed and/or associated with immune cells have been discovered too [ 66 , 108 , 147 ].…”
Section: Milk Evs In Cross-organism and Cross-species Communicatiomentioning
confidence: 99%
“…Another study [ 69 ] assessed the effect of exosomes from commercial cow’s milk in dextran sulfate sodium–induced colitis in a murine model. They noticed an improvement in several features of the dextran sulfate sodium–induced colitis, a modulation of the gut microbiota as well as a restored intestinal permeability and replenished mucin secretion.…”
Section: Evidence About the Influence Of Milk Exosome-derived Mirnmentioning
confidence: 99%